Wear-resistant nylon product with heat conduction function and preparation method thereof

By blending the copper-aminated carbon fiber-graphene oxide composite with carboxylated nylon 6 resin, combined with nano β-silicon nitride and antioxidants, the problems of insufficient thermal conductivity and mechanical properties of nylon materials are solved, and the problem of insufficient thermal conductivity and degradation of mechanical properties is achieved. Improved thermal conductivity and wear resistance.

CN119144150AActive Publication Date: 2024-12-17JIANGSU XUXIN MASCH MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411667410.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-17
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

Traditional nylon materials have limitations in thermal conductivity, resulting in limited application range, and the large addition of thermal fillers will lead to a decrease in mechanical properties.

Method used

By blending the copper-plated carbon fiber-graphene oxide composite with carboxylated nylon 6 resin, a heat conduction path is formed and dispersibility is improved. Combined with nano β-silicon nitride and antioxidants, the preparation method of nylon products is optimized to improve heat conductivity to improve heat conductivity. and wear resistance.

Benefits of technology

It significantly improves the thermal conductivity and wear resistance of nylon products, avoids the decline in mechanical properties caused by packing agglomeration, and expands the application range of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of nylon, in particular to a wear-resistant nylon product with a heat conduction function and a preparation method of the wear-resistant nylon product. According to the invention, hexachlorocyclotriphosphazene is used as a raw material to prepare a cyclotriphosphazene compound, the compound has six terminal carboxyl groups, and then the cyclotriphosphazene compound is used as an inner core to prepare the carboxylated nylon 6 resin with good mechanical properties and thermal properties. A nylon product prepared by using the carboxylated nylon 6 resin as a raw material is excellent in wear resistance. And copper is plated on the carbon fiber-graphene oxide compound, so that a relatively good heat-conducting channel is formed, and the heat-conducting property of the nylon product is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nylon, in particular to a wear-resistant nylon product with heat-conducting function and a preparation method thereof. Background Art

[0002] In the field of modern industry and consumer goods, nylon, as an important engineering plastic, is widely used due to its excellent wear resistance, strength and chemical corrosion resistance. However, traditional nylon materials have limitations in thermal conductivity, which limits the application scope of nylon materials.

[0003] The prior art generally improves the thermal conductivity of nylon by introducing thermally conductive fillers or additives into the nylon matrix. Thermally conductive fillers can be metal particles, carbon nanotubes, graphite, etc. These fillers have excellent thermal conductivity and can improve the thermal conductivity of nylon products. However, the addition of a large amount of fillers will cause the fillers to agglomerate and be difficult to disperse, thereby causing the mechanical properties of nylon products to deteriorate.

[0004] In order to solve the above problems and improve the thermal conductivity and wear resistance of nylon products, the present invention provides a wear-resistant nylon product with thermal conductivity function and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a wear-resistant nylon product with heat-conducting function and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a wear-resistant nylon product with heat-conducting function comprises the following steps: S1: taking the activated aminated carbon fiber-graphene oxide composite and placing it in a plating solution for chemical copper plating, the reaction time is 5-10min, precipitating, centrifuging, washing, and drying to obtain a copper-plated aminated carbon fiber-graphene oxide composite; S2: taking carboxylated nylon 6 resin, adding nano-β-silicon nitride, copper-plated amino carbon fiber-graphene oxide composite, antioxidant, lubricant, blending, cooling and pelletizing, injection molding, and obtaining nylon products; More optimally, the preparation method of the amino carbon fiber-graphene oxide composite is: take γ-aminopropyltriethoxysilane and methanol aqueous solution, stir evenly, add carbon fiber-graphene oxide composite, heat to 65-70°C, stir for 1-2h, filter, wash, and dry to obtain the pretreated carbon fiber-graphene oxide composite; take succinic anhydride and ethylene glycolamine, mix evenly, add the pretreated carbon fiber-graphene oxide composite and p-toluenesulfonic acid, heat to 105-110°C, stir for 4-5h, filter, wash, and dry to obtain the amino carbon fiber-graphene oxide composite; More optimally, the preparation method of the carbon fiber-graphene oxide composite is: take carbon fiber and anhydrous ethanol, ultrasonically disperse for 10-14 hours, and dry to obtain cleaned carbon fiber; take graphene oxide and deionized water, ultrasonically disperse to obtain graphene oxide dispersion; take deionized water and anhydrous ethanol, mix evenly, add silane coupling agent KH550, heat to 40-45°C, stir for 2-3 hours, add the cleaned carbon fiber, stir for 2-3 hours, add graphene oxide dispersion, drop hydrochloric acid, adjust the pH value to 3, heat to 75-80°C, react for 2-3 hours, wash and dry to obtain a carbon fiber-graphene oxide composite.

[0007] More optimally, the nylon product comprises the following ingredients, calculated by weight: 100-115 parts of carboxylated nylon 6 resin, 10-15 parts of nano-β-silicon nitride, 10-15 parts of copper-plated amino carbon fiber-graphene oxide composite, 0.05-0.1 parts of antioxidant, and 0.05-0.1 parts of lubricant.

[0008] Preferably, the preparation method of the carboxylated nylon 6 resin comprises the following steps: S1: Take hexachlorocyclotriphosphazene and tetrahydrofuran, stir evenly to obtain a mixed solution; take anhydrous potassium carbonate, p-hydroxybenzaldehyde, and tetrahydrofuran, stir evenly, add the mixed solution, heat to 65-70°C, reflux for 22-26h, filter, rotary evaporate, precipitate, filter, wash, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene; S2: Take hexa(4-formylphenoxy)cyclotriphosphazene, sodium hydroxide, tetrahydrofuran, and distilled water, stir evenly, add potassium permanganate, filter, rotary evaporate, add hydrochloric acid, adjust the pH value to 3-4, precipitate, filter, wash, and dry to obtain a cyclotriphosphazene compound; S3: Take ε-caprolactam, cyclotriphosphazene compounds and distilled water, raise the temperature to 250-252°C in a nitrogen environment, react for 3-4 hours, vacuum react for 2-2.5 hours, then extract the material in deionized water at 100°C for 22-26 hours, and dry to obtain carboxylated nylon 6 resin.

[0009] More optimally, the lubricant is any one or more of oleamide, glyceryl stearate, and calcium stearate.

[0010] More optimally, the antioxidant is any one or more of phosphite, 2,6-di-tert-butyl-p-cresol, and didodecanol ester.

[0011] More optimally, in step 1, the preparation method of the activated aminated carbon fiber-graphene oxide composite is: take stannous chloride and hydrochloric acid, stir evenly to obtain a sensitizing solution; take palladium chloride and hydrochloric acid, stir evenly to obtain an activation solution; take the sensitizing solution, add the aminated carbon fiber-graphene oxide composite, stir evenly, wash, filter, add the activation solution, stir evenly, wash, filter, and obtain the activated aminated carbon fiber-graphene oxide composite; The preparation method of the plating solution is as follows: copper sulfate pentahydrate, deionized water, and formaldehyde solution are taken, and stirred evenly to obtain solution A; anhydrous sodium carbonate, deionized water, and potassium sodium tartrate are stirred evenly to obtain solution B; solution A is added to solution B, and mixed evenly to obtain a plating solution.

[0012] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) The present invention first uses hexachlorocyclotriphosphazene as a raw material to prepare a cyclotriphosphazene compound having six terminal carboxyl groups, and then uses the cyclotriphosphazene compound as a core to prepare a carboxylated nylon 6 resin having good mechanical and thermal properties. The nylon product prepared using the carboxylated nylon 6 resin as a raw material has excellent wear resistance.

[0013] (2) The present invention combines carbon fiber and graphene oxide to improve the dispersion performance of graphene oxide, and copper is plated on the carbon fiber-graphene oxide composite, thereby forming a better heat conduction path and enhancing the thermal conductivity of nylon products. The carbon fiber-graphene oxide composite is subjected to an amination treatment, and the amino groups on the copper-plated amination carbon fiber-graphene oxide composite can react with the carboxyl groups on the carboxylated nylon 6 resin, thereby improving the dispersion of the copper-plated amination carbon fiber-graphene oxide composite in the matrix, thereby improving the wear resistance and thermal conductivity of the nylon product. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] The purchase manufacturers and models of the raw materials involved in the present invention are not particularly limited, and exemplary examples include: Nano-β-silicon nitride: particle size: 25nm; carbon fiber diameter is 50-200nm, length is 1-15µm, provided by Xi'an Qiyue Biotechnology Co., Ltd.; graphite powder: model: G616494, provided by Aladdin; The preparation method of graphene oxide in the present invention is: Take 5g potassium permanganate, 1g graphite powder, and 70mL 98wt% sulfuric acid, mix well, cool to 0°C in an ice bath, heat to 80°C, stir evenly and react for 10h, add 100mL deionized water, stir evenly, heat to 90°C, add 200mL deionized water and 3mL 30wt% hydrogen peroxide, filter, take the supernatant, wash until the pH is neutral, freeze-dry, and sieve to obtain graphene oxide with a thickness of 10-20nm.

[0016] Embodiment 1: A method for preparing a wear-resistant nylon product with heat-conducting function, comprising the following steps: Step 1: Preparation of carboxylated nylon 6 resin: Take 50g of hexachlorocyclotriphosphazene and 100mL of tetrahydrofuran, stir evenly to obtain a mixed solution; take 140g of anhydrous potassium carbonate, 125g of p-hydroxybenzaldehyde, and 500mL of tetrahydrofuran, stir evenly, add the mixed solution, heat to 67°C, reflux for 24h, filter, rotary evaporate, precipitate, filter, wash, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene; Take 50g of hexa(4-formylphenoxy)cyclotriphosphazene, 15g of sodium hydroxide, 300mL of tetrahydrofuran, and 300mL of distilled water, stir evenly, add 118g of potassium permanganate, filter with suction, rotary evaporate, add hydrochloric acid, adjust the pH value to 3.5, precipitate, filter with suction, wash, and dry to obtain a cyclotriphosphazene compound; Take 2000g of ε-caprolactam, 50g of cyclotriphosphazene compound, and 60g of distilled water, heat to 251°C in a nitrogen environment, react for 3.5h, vacuum react for 2.2h, then extract the material in deionized water at 100°C for 24h, and dry to obtain carboxylated nylon 6 resin; Step 2: Preparation of carbon fiber-graphene oxide composite: Take 2g of carbon fiber and 500mL of anhydrous ethanol, ultrasonically disperse for 12h, and dry to obtain cleaned carbon fiber; take 0.2g of graphene oxide and 500mL of deionized water, ultrasonically disperse to obtain graphene oxide dispersion; take 150mL of deionized water and 350mL of anhydrous ethanol, mix evenly, add 0.8g of silane coupling agent KH550, heat to 42°C, stir for 2.5h, add 2g of cleaned carbon fiber, stir for 2.5h, add graphene oxide dispersion, drop hydrochloric acid, adjust the pH value to 3, heat to 78°C, react for 2.5h, wash and dry to obtain a carbon fiber-graphene oxide composite; Step 3: Preparation of amino carbon fiber-graphene oxide composite: Take 8g of γ-aminopropyltriethoxysilane and 80g of a 10% methanol aqueous solution, stir evenly, add 30g of a carbon fiber-graphene oxide composite, heat to 68°C, stir for 1.5h, filter, wash, and dry to obtain a pretreated carbon fiber-graphene oxide composite; take 3g of succinic anhydride and 45g of ethylene glycolamine, mix evenly, add 25g of the pretreated carbon fiber-graphene oxide composite and 1g of p-toluenesulfonic acid, heat to 108°C, stir for 4.5h, filter, wash, and dry to obtain an amino carbon fiber-graphene oxide composite; Step 4: Preparation of copper-plated amino carbon fiber-graphene oxide composite: Take 0.0075 mol / L of stannous chloride and 0.15 mol / L of hydrochloric acid, stir evenly to obtain a sensitizing solution; take 0.003 mol / L of palladium chloride and 0.06 mol / L of hydrochloric acid, stir evenly to obtain an activation solution; take 100 mL of the sensitizing solution, add 2 g of the amino carbon fiber-graphene oxide composite, stir evenly, wash, filter, add 100 mL of the activation solution, stir evenly, wash, filter, and obtain the activated amino carbon fiber-graphene oxide composite; Take 5g of copper sulfate pentahydrate, 300ml of deionized water, and 8ml of 37% formaldehyde solution, stir evenly to obtain solution A; add 8g of anhydrous sodium carbonate, 300ml of deionized water, and 30g of potassium sodium tartrate, stir evenly to obtain solution B; add solution A to solution B, mix evenly, and obtain a plating solution; 2 g of the activated aminated carbon fiber-graphene oxide composite was placed in a plating solution for chemical copper plating for 5 min, followed by precipitation, centrifugation, washing, and drying to obtain a copper-plated aminated carbon fiber-graphene oxide composite; Step 5: Preparation of nylon products: Take carboxylated nylon 6 resin, add nano-β-silicon nitride, copper-plated amino carbon fiber-graphene oxide composite, antioxidant, lubricant, blend, cool and pelletize, and injection mold to obtain nylon products; The nylon product comprises the following components, calculated by weight: 112 parts of carboxylated nylon 6 resin, 12 parts of nano-β-silicon nitride, 13 parts of copper-plated amino carbon fiber-graphene oxide composite, 0.08 parts of antioxidant, and 0.08 parts of lubricant; The lubricant is oleic acid amide; the antioxidant is phosphite.

[0017] Embodiment 2: A method for preparing a wear-resistant nylon product with heat-conducting function, comprising the following steps: Step 1: Preparation of carboxylated nylon 6 resin: Take 50g of hexachlorocyclotriphosphazene and 100mL of tetrahydrofuran, stir evenly to obtain a mixed solution; take 140g of anhydrous potassium carbonate, 125g of p-hydroxybenzaldehyde, and 500mL of tetrahydrofuran, stir evenly, add the mixed solution, heat to 65°C, reflux for 22h, filter, rotary evaporate, precipitate, filter, wash, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene; Take 50g of hexa(4-formylphenoxy)cyclotriphosphazene, 15g of sodium hydroxide, 300mL of tetrahydrofuran, and 300mL of distilled water, stir evenly, add 118g of potassium permanganate, filter with suction, rotary evaporate, add hydrochloric acid, adjust the pH value to 3, precipitate, filter with suction, wash, and dry to obtain a cyclotriphosphazene compound; Take 2000g of ε-caprolactam, 50g of cyclotriphosphazene compound, and 60g of distilled water, heat to 250°C in a nitrogen environment, react for 3h, vacuum react for 2h, then extract the material in deionized water at 100°C for 22h, and dry to obtain carboxylated nylon 6 resin; Step 2: Preparation of carbon fiber-graphene oxide composite: Take 2g of carbon fiber and 500mL of anhydrous ethanol, ultrasonically disperse for 10h, and dry to obtain cleaned carbon fiber; take 0.2g of graphene oxide and 500mL of deionized water, ultrasonically disperse to obtain graphene oxide dispersion; take 150mL of deionized water and 350mL of anhydrous ethanol, mix evenly, add 0.8g of silane coupling agent KH550, heat to 40°C, stir for 2h, add 2g of cleaned carbon fiber, stir for 2h, add graphene oxide dispersion, drop hydrochloric acid, adjust the pH value to 3, heat to 75°C, react for 2h, wash and dry to obtain a carbon fiber-graphene oxide composite; Step 3: Preparation of amino carbon fiber-graphene oxide composite: Take 8g of γ-aminopropyltriethoxysilane and 80g of a 10% methanol aqueous solution, stir evenly, add 30g of a carbon fiber-graphene oxide composite, heat to 65°C, stir for 1h, filter, wash, and dry to obtain a pretreated carbon fiber-graphene oxide composite; take 3g of succinic anhydride and 45g of ethylene glycolamine, mix evenly, add 25g of the pretreated carbon fiber-graphene oxide composite and 1g of p-toluenesulfonic acid, heat to 105°C, stir for 4h, filter, wash, and dry to obtain an amino carbon fiber-graphene oxide composite; Step 4: Preparation of copper-plated amino carbon fiber-graphene oxide composite: Take 0.0075 mol / L of stannous chloride and 0.15 mol / L of hydrochloric acid, stir evenly to obtain a sensitizing solution; take 0.003 mol / L of palladium chloride and 0.06 mol / L of hydrochloric acid, stir evenly to obtain an activation solution; take 100 mL of the sensitizing solution, add 2 g of the amino carbon fiber-graphene oxide composite, stir evenly, wash, filter, add 100 mL of the activation solution, stir evenly, wash, filter, and obtain the activated amino carbon fiber-graphene oxide composite; Take 5g of copper sulfate pentahydrate, 300ml of deionized water, and 8ml of 37% formaldehyde solution, stir evenly to obtain solution A; add 8g of anhydrous sodium carbonate, 300ml of deionized water, and 30g of potassium sodium tartrate, stir evenly to obtain solution B; add solution A to solution B, mix evenly, and obtain a plating solution; 2 g of the activated aminated carbon fiber-graphene oxide composite was placed in a plating solution for chemical copper plating for 5 min, followed by precipitation, centrifugation, washing, and drying to obtain a copper-plated aminated carbon fiber-graphene oxide composite; Step 5: Preparation of nylon products: Take carboxylated nylon 6 resin, add nano-β-silicon nitride, copper-plated amino carbon fiber-graphene oxide composite, antioxidant, lubricant, blend, cool and pelletize, and injection mold to obtain nylon products; The nylon product comprises the following components, calculated by weight: 100 parts of carboxylated nylon 6 resin, 10 parts of nano-β-silicon nitride, 10 parts of copper-plated amino carbon fiber-graphene oxide composite, 0.05 parts of antioxidant, and 0.05 parts of lubricant; The lubricant is glyceryl stearate; and the antioxidant is 2,6-di-tert-butyl-p-cresol.

[0018] Embodiment 3: A method for preparing a wear-resistant nylon product with heat-conducting function, comprising the following steps: Step 1: Preparation of carboxylated nylon 6 resin: Take 50g of hexachlorocyclotriphosphazene and 100mL of tetrahydrofuran, stir evenly to obtain a mixed solution; take 140g of anhydrous potassium carbonate, 125g of p-hydroxybenzaldehyde, and 500mL of tetrahydrofuran, stir evenly, add the mixed solution, heat to 70°C, reflux for 26h, filter, rotary evaporate, precipitate, filter, wash, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene; Take 50g of hexa(4-formylphenoxy)cyclotriphosphazene, 15g of sodium hydroxide, 300mL of tetrahydrofuran, and 300mL of distilled water, stir evenly, add 118g of potassium permanganate, filter with suction, rotary evaporate, add hydrochloric acid, adjust the pH value to 4, precipitate, filter with suction, wash, and dry to obtain a cyclotriphosphazene compound; Take 2000g of ε-caprolactam, 50g of cyclotriphosphazene compound, and 60g of distilled water, heat to 252°C in a nitrogen environment, react for 4h, vacuum react for 2.5h, then extract the material in deionized water at 100°C for 26h, and dry to obtain carboxylated nylon 6 resin; Step 2: Preparation of carbon fiber-graphene oxide composite: Take 2g of carbon fiber and 500mL of anhydrous ethanol, ultrasonically disperse for 14h, and dry to obtain cleaned carbon fiber; take 0.2g of graphene oxide and 500mL of deionized water, ultrasonically disperse to obtain graphene oxide dispersion; take 150mL of deionized water and 350mL of anhydrous ethanol, mix evenly, add 0.8g of silane coupling agent KH550, heat to 45°C, stir for 3h, add 2g of cleaned carbon fiber, stir for 3h, add graphene oxide dispersion, drop hydrochloric acid, adjust the pH value to 3, heat to 80°C, react for 3h, wash and dry to obtain a carbon fiber-graphene oxide composite; Step 3: Preparation of amino carbon fiber-graphene oxide composite: Take 8g of γ-aminopropyltriethoxysilane and 80g of a 10% methanol aqueous solution, stir evenly, add 30g of a carbon fiber-graphene oxide composite, heat to 70°C, stir for 2h, filter, wash, and dry to obtain a pretreated carbon fiber-graphene oxide composite; take 3g of succinic anhydride and 45g of ethylene glycolamine, mix evenly, add 25g of the pretreated carbon fiber-graphene oxide composite and 1g of p-toluenesulfonic acid, heat to 110°C, stir for 5h, filter, wash, and dry to obtain an amino carbon fiber-graphene oxide composite; Step 4: Preparation of copper-plated amino carbon fiber-graphene oxide composite: Take 0.0075 mol / L of stannous chloride and 0.15 mol / L of hydrochloric acid, stir evenly to obtain a sensitizing solution; take 0.003 mol / L of palladium chloride and 0.06 mol / L of hydrochloric acid, stir evenly to obtain an activation solution; take 100 mL of the sensitizing solution, add 2 g of the amino carbon fiber-graphene oxide composite, stir evenly, wash, filter, add 100 mL of the activation solution, stir evenly, wash, filter, and obtain the activated amino carbon fiber-graphene oxide composite; Take 5g of copper sulfate pentahydrate, 300ml of deionized water, and 8ml of 37% formaldehyde solution, stir evenly to obtain solution A; add 8g of anhydrous sodium carbonate, 300ml of deionized water, and 30g of potassium sodium tartrate, stir evenly to obtain solution B; add solution A to solution B, mix evenly, and obtain a plating solution; 2 g of the activated aminated carbon fiber-graphene oxide composite was placed in a plating solution for chemical copper plating for 5 min, followed by precipitation, centrifugation, washing, and drying to obtain a copper-plated aminated carbon fiber-graphene oxide composite; Step 5: Preparation of nylon products: Take carboxylated nylon 6 resin, add nano-β-silicon nitride, copper-plated amino carbon fiber-graphene oxide composite, antioxidant, lubricant, blend, cool and pelletize, and injection mold to obtain nylon products; The nylon product comprises the following components, measured by weight: 115 parts of carboxylated nylon 6 resin, 15 parts of nano-β-silicon nitride, 15 parts of copper-plated amino carbon fiber-graphene oxide composite, 0.1 parts of antioxidant, and 0.1 parts of lubricant; The lubricant is calcium stearate; the antioxidant is didodecyl alcohol ester.

[0019] Comparative Example 1: No copper plating is performed on the carbon fiber-graphene oxide composite, and the rest is the same as in Example 1: Step 1: Preparation of carboxylated nylon 6 resin: Take 50g of hexachlorocyclotriphosphazene and 100mL of tetrahydrofuran, stir evenly to obtain a mixed solution; take 140g of anhydrous potassium carbonate, 125g of p-hydroxybenzaldehyde, and 500mL of tetrahydrofuran, stir evenly, add the mixed solution, heat to 67°C, reflux for 24h, filter, rotary evaporate, precipitate, filter, wash, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene; Take 50g of hexa(4-formylphenoxy)cyclotriphosphazene, 15g of sodium hydroxide, 300mL of tetrahydrofuran, and 300mL of distilled water, stir evenly, add 118g of potassium permanganate, filter with suction, rotary evaporate, add hydrochloric acid, adjust the pH value to 3.5, precipitate, filter with suction, wash, and dry to obtain a cyclotriphosphazene compound; Take 2000g of ε-caprolactam, 50g of cyclotriphosphazene compound, and 60g of distilled water, heat to 251°C in a nitrogen environment, react for 3.5h, vacuum react for 2.2h, then extract the material in deionized water at 100°C for 24h, and dry to obtain carboxylated nylon 6 resin; Step 2: Preparation of carbon fiber-graphene oxide composite: Take 2g of carbon fiber and 500mL of anhydrous ethanol, ultrasonically disperse for 12h, and dry to obtain cleaned carbon fiber; take 0.2g of graphene oxide and 500mL of deionized water, ultrasonically disperse to obtain graphene oxide dispersion; take 150mL of deionized water and 350mL of anhydrous ethanol, mix evenly, add 0.8g of silane coupling agent KH550, heat to 42°C, stir for 2.5h, add 2g of cleaned carbon fiber, stir for 2.5h, add graphene oxide dispersion, drop hydrochloric acid, adjust the pH value to 3, heat to 78°C, react for 2.5h, wash and dry to obtain a carbon fiber-graphene oxide composite; Step 3: Preparation of amino carbon fiber-graphene oxide composite: Take 8g of γ-aminopropyltriethoxysilane and 80g of a 10% methanol aqueous solution, stir evenly, add 30g of a carbon fiber-graphene oxide composite, heat to 68°C, stir for 1.5h, filter, wash, and dry to obtain a pretreated carbon fiber-graphene oxide composite; take 3g of succinic anhydride and 45g of ethylene glycolamine, mix evenly, add 25g of the pretreated carbon fiber-graphene oxide composite and 1g of p-toluenesulfonic acid, heat to 108°C, stir for 4.5h, filter, wash, and dry to obtain an amino carbon fiber-graphene oxide composite; Step 4: Preparation of nylon products: Take carboxylated nylon 6 resin, add nano-β-silicon nitride, amino carbon fiber-graphene oxide composite, antioxidant, lubricant, blend, cool and pelletize, and injection mold to obtain nylon products; The nylon product comprises the following components, calculated by weight: 112 parts of carboxylated nylon 6 resin, 12 parts of nano-β-silicon nitride, 13 parts of amino carbon fiber-graphene oxide composite, 0.08 parts of antioxidant, and 0.08 parts of lubricant; The lubricant is oleic acid amide; the antioxidant is phosphite.

[0020] Comparative Example 2: The carbon fiber-graphene oxide composite is not subjected to amination treatment, and the rest is the same as Example 1: Step 1: Preparation of carboxylated nylon 6 resin: Take 50g of hexachlorocyclotriphosphazene and 100mL of tetrahydrofuran, stir evenly to obtain a mixed solution; take 140g of anhydrous potassium carbonate, 125g of p-hydroxybenzaldehyde, and 500mL of tetrahydrofuran, stir evenly, add the mixed solution, heat to 67°C, reflux for 24h, filter, rotary evaporate, precipitate, filter, wash, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene; Take 50g of hexa(4-formylphenoxy)cyclotriphosphazene, 15g of sodium hydroxide, 300mL of tetrahydrofuran, and 300mL of distilled water, stir evenly, add 118g of potassium permanganate, filter with suction, rotary evaporate, add hydrochloric acid, adjust the pH value to 3.5, precipitate, filter with suction, wash, and dry to obtain a cyclotriphosphazene compound; Take 2000g of ε-caprolactam, 50g of cyclotriphosphazene compound, and 60g of distilled water, heat to 251°C in a nitrogen environment, react for 3.5h, vacuum react for 2.2h, then extract the material in deionized water at 100°C for 24h, and dry to obtain carboxylated nylon 6 resin; Step 2: Preparation of carbon fiber-graphene oxide composite: Take 2g of carbon fiber and 500mL of anhydrous ethanol, ultrasonically disperse for 12h, and dry to obtain cleaned carbon fiber; take 0.2g of graphene oxide and 500mL of deionized water, ultrasonically disperse to obtain graphene oxide dispersion; take 150mL of deionized water and 350mL of anhydrous ethanol, mix evenly, add 0.8g of silane coupling agent KH550, heat to 42°C, stir for 2.5h, add 2g of cleaned carbon fiber, stir for 2.5h, add graphene oxide dispersion, drop hydrochloric acid, adjust the pH value to 3, heat to 78°C, react for 2.5h, wash and dry to obtain a carbon fiber-graphene oxide composite; Step 3: Preparation of copper-coated carbon fiber-graphene oxide composite: Take 0.0075 mol / L of stannous chloride and 0.15 mol / L of hydrochloric acid, stir evenly to obtain a sensitizing solution; take 0.003 mol / L of palladium chloride and 0.06 mol / L of hydrochloric acid, stir evenly to obtain an activation solution; take 100 mL of the sensitizing solution, add 2 g of the carbon fiber-graphene oxide composite, stir evenly, wash, filter, add 100 mL of the activation solution, stir evenly, wash, filter, and obtain an activated carbon fiber-graphene oxide composite; Take 5g of copper sulfate pentahydrate, 300ml of deionized water, and 8ml of 37% formaldehyde solution, stir evenly to obtain solution A; add 8g of anhydrous sodium carbonate, 300ml of deionized water, and 30g of potassium sodium tartrate, stir evenly to obtain solution B; add solution A to solution B, mix evenly, and obtain a plating solution; 2 g of the activated carbon fiber-graphene oxide composite was placed in a plating solution for chemical copper plating for 5 min, followed by precipitation, centrifugation, washing, and drying to obtain a copper-plated carbon fiber-graphene oxide composite; Step 4: Preparation of nylon products: Take carboxylated nylon 6 resin, add nano-β-silicon nitride, copper-plated carbon fiber-graphene oxide composite, antioxidant, lubricant, blend, cool and pelletize, and injection mold to obtain nylon products; The nylon product comprises the following components, measured by weight: 112 parts of carboxylated nylon 6 resin, 12 parts of nano-β-silicon nitride, 13 parts of copper-plated carbon fiber-graphene oxide composite, 0.08 parts of antioxidant, and 0.08 parts of lubricant; The lubricant is oleic acid amide; the antioxidant is phosphite.

[0021] Comparative Example 3: No carbon fiber is added, and the rest is the same as Example 1: Step 1: Preparation of carboxylated nylon 6 resin: Take 50g of hexachlorocyclotriphosphazene and 100mL of tetrahydrofuran, stir evenly to obtain a mixed solution; take 140g of anhydrous potassium carbonate, 125g of p-hydroxybenzaldehyde, and 500mL of tetrahydrofuran, stir evenly, add the mixed solution, heat to 67°C, reflux for 24h, filter, rotary evaporate, precipitate, filter, wash, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene; Take 50g of hexa(4-formylphenoxy)cyclotriphosphazene, 15g of sodium hydroxide, 300mL of tetrahydrofuran, and 300mL of distilled water, stir evenly, add 118g of potassium permanganate, filter with suction, rotary evaporate, add hydrochloric acid, adjust the pH value to 3.5, precipitate, filter with suction, wash, and dry to obtain a cyclotriphosphazene compound; Take 2000g of ε-caprolactam, 50g of cyclotriphosphazene compound, and 60g of distilled water, heat to 251°C in a nitrogen environment, react for 3.5h, vacuum react for 2.2h, then extract the material in deionized water at 100°C for 24h, and dry to obtain carboxylated nylon 6 resin; Step 2: Preparation of amination graphene: Take 8g of γ-aminopropyltriethoxysilane and 80g of a 10% methanol aqueous solution, stir evenly, add 30g of graphene oxide, heat to 68°C, stir for 1.5h, filter, wash, and dry to obtain pretreated graphene; take 3g of succinic anhydride and 45g of ethylene glycolamine, mix evenly, add 25g of pretreated graphene and 1g of p-toluenesulfonic acid, heat to 108°C, stir for 4.5h, filter, wash, and dry to obtain amino graphene; Step 3: Preparation of copper-plated graphene: Take 0.0075 mol / L of stannous chloride and 0.15 mol / L of hydrochloric acid, stir evenly to obtain a sensitizing solution; take 0.003 mol / L of palladium chloride and 0.06 mol / L of hydrochloric acid, stir evenly to obtain an activating solution; take 100 mL of the sensitizing solution, add 2 g of the amino-modified carbon fiber-graphene oxide composite, stir evenly, wash, filter, add 100 mL of the activating solution, stir evenly, wash, filter, and obtain activated graphene; Take 5g of copper sulfate pentahydrate, 300ml of deionized water, and 8ml of 37% formaldehyde solution, stir evenly to obtain solution A; add 8g of anhydrous sodium carbonate, 300ml of deionized water, and 30g of potassium sodium tartrate, stir evenly to obtain solution B; add solution A to solution B, mix evenly, and obtain a plating solution; 2 g of activated graphene was placed in a plating solution for chemical copper plating for 5 min, followed by precipitation, centrifugation, washing, and drying to obtain copper-plated graphene; Step 4: Preparation of nylon products: Take carboxylated nylon 6 resin, add nano-β-silicon nitride, copper-plated graphene, antioxidant, and lubricant, blend, cool and pelletize, and injection mold to obtain a nylon product; The nylon product comprises the following components, measured in parts by weight: 112 parts of carboxylated nylon 6 resin, 12 parts of nano-β-silicon nitride, 13 parts of copper-plated graphene, 0.08 parts of antioxidant, and 0.08 parts of lubricant; The lubricant is oleic acid amide; the antioxidant is phosphite.

[0022] experiment: The nylon products prepared in Examples 1-3 and Comparative Examples 1-3 were used for performance testing. The tensile strength of the nylon products was tested with reference to ASTM-D638; the dynamic friction coefficient of the nylon products was tested with reference to GB 3960-2023; the thermal conductivity of the obtained nylon products was tested using a thermal constant analyzer, and the data are as follows:

[0023] Conclusion: Comparative Example 1 does not plate copper on the carbon fiber-graphene oxide composite, and the thermal conductivity of the nylon product is significantly reduced. Examples 1-3 plate copper on the carbon fiber-graphene oxide composite, thereby forming a better thermal conductivity path and enhancing the thermal conductivity of the nylon product. Comparative Example 2 does not perform amination treatment on the carbon fiber-graphene oxide composite, and Examples 1-3 compound the carbon fiber and graphene oxide together, thereby improving the dispersion performance of graphene oxide. The amino group on the copper-plated amination carbon fiber-graphene oxide composite can also react with the carboxyl group on the carboxylated nylon 6 resin to improve the dispersion of the copper-plated amination carbon fiber-graphene oxide composite in the matrix, thereby improving the wear resistance and thermal conductivity of the nylon product. Comparative Example 3 does not add carbon fiber, and the wear resistance and thermal conductivity of the nylon product are both reduced.

[0024] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant nylon product with heat-conducting function, characterized in that: The following steps are involved: Step 1: taking the activated aminated carbon fiber-graphene oxide composite and placing it in a plating solution for chemical copper plating, the reaction time is 5-10 minutes, precipitating, centrifuging, washing, and drying to obtain a copper-plated aminated carbon fiber-graphene oxide composite; Step 2: Take carboxylated nylon 6 resin, add nano-β-silicon nitride, copper-plated amino carbon fiber-graphene oxide composite, antioxidant, lubricant, blend, cool and pelletize, and injection mold to obtain nylon products; The preparation method of the amino carbon fiber-graphene oxide composite is as follows: taking γ-aminopropyltriethoxysilane and methanol aqueous solution, stirring evenly, adding the carbon fiber-graphene oxide composite, heating to 65-70° C., stirring for 1-2 hours, filtering, washing, and drying to obtain the pretreated carbon fiber-graphene oxide composite; taking succinic anhydride and ethylene glycolamine, mixing evenly, adding the pretreated carbon fiber-graphene oxide composite and p-toluenesulfonic acid, heating to 105-110° C., stirring for 4-5 hours, filtering, washing, and drying to obtain the amino carbon fiber-graphene oxide composite; The preparation method of the carbon fiber-graphene oxide composite is as follows: taking carbon fiber and anhydrous ethanol, ultrasonically dispersing for 10-14 hours, and drying to obtain cleaned carbon fiber; taking graphene oxide and deionized water, ultrasonically dispersing to obtain graphene oxide dispersion; taking deionized water and anhydrous ethanol, mixing evenly, adding silane coupling agent KH550, heating to 40-45° C., stirring for 2-3 hours, adding the cleaned carbon fiber, stirring for 2-3 hours, adding graphene oxide dispersion, dripping hydrochloric acid, adjusting the pH value to 3, heating to 75-80° C., reacting for 2-3 hours, washing, and drying to obtain the carbon fiber-graphene oxide composite.

2. The method for preparing a wear-resistant nylon product with heat-conducting function according to claim 1, characterized in that: The nylon product comprises the following components, calculated by weight: 100-115 parts of carboxylated nylon 6 resin, 10-15 parts of nano-β-silicon nitride, 10-15 parts of copper-plated amino carbon fiber-graphene oxide composite, 0.05-0.1 parts of antioxidant, and 0.05-0.1 parts of lubricant.

3. The method for preparing a wear-resistant nylon product with heat-conducting function according to claim 1, characterized in that: The preparation method of the carboxylated nylon 6 resin is: The following steps are involved: S1: Take hexachlorocyclotriphosphazene and tetrahydrofuran, stir evenly to obtain a mixed solution; take anhydrous potassium carbonate, p-hydroxybenzaldehyde, and tetrahydrofuran, stir evenly, add the mixed solution, heat to 65-70°C, reflux for 22-26h, filter, rotary evaporate, precipitate, filter, wash, and dry to obtain hexa(4-formylphenoxy)cyclotriphosphazene; S2: Take hexa(4-formylphenoxy)cyclotriphosphazene, sodium hydroxide, tetrahydrofuran, and distilled water, stir evenly, add potassium permanganate, filter, rotary evaporate, add hydrochloric acid, adjust the pH value to 3-4, precipitate, filter, wash, and dry to obtain a cyclotriphosphazene compound; S3: Take ε-caprolactam, cyclotriphosphazene compounds and distilled water, raise the temperature to 250-252°C in a nitrogen environment, react for 3-4 hours, vacuum react for 2-2.5 hours, then extract the material in deionized water at 100°C for 22-26 hours, and dry to obtain carboxylated nylon 6 resin.

4. The method for preparing a wear-resistant nylon product with heat-conducting function according to claim 1, characterized in that: The lubricant is any one or more of oleamide, glyceryl stearate, and calcium stearate.

5. The method for preparing a wear-resistant nylon product with heat-conducting function according to claim 1, characterized in that: The antioxidant is any one or more of phosphite, 2,6-di-tert-butyl-p-cresol, and didodecanol ester.

6. The method for preparing a wear-resistant nylon product with heat-conducting function according to claim 1, characterized in that: In step 1, the preparation method of the activated aminated carbon fiber-graphene oxide composite is as follows: take stannous chloride and hydrochloric acid, stir evenly, and obtain a sensitizing solution; take palladium chloride and hydrochloric acid, stir evenly, and obtain an activation solution; take the sensitizing solution, add the aminated carbon fiber-graphene oxide composite, stir evenly, wash, filter, add the activation solution, stir evenly, wash, filter, and obtain the activated aminated carbon fiber-graphene oxide composite; The preparation method of the plating solution is as follows: copper sulfate pentahydrate, deionized water, and formaldehyde solution are taken, and stirred evenly to obtain solution A; anhydrous sodium carbonate, deionized water, and potassium sodium tartrate are stirred evenly to obtain solution B; solution A is added to solution B, and mixed evenly to obtain a plating solution.

7. A nylon product prepared according to the method for preparing a wear-resistant nylon product with heat-conducting function according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Interface-enhanced carbon fiber / polycaprolactam composite material and preparation method thereof

    CN102493184A

  • Preparation method of composite carbon fiber / graphene oxide / organosilicone resin multidimensional hybrid material

    CN104151581A

  • Cobalt / graphene composite nano wave-absorbing material and preparation method thereof

    CN104209531A

  • Branched modifier and corresponding flame retardant nylon resin

    CN105017525A

  • Method of chemically-grafting graphene oxide onto surface of carbon fiber

    CN105239357A